Cybersecurity and local government - Norris, Donald F.; Mateczun, Laura; Forno, Richard (John Wiley & Sons, Inc., 2022)
"This book begins with a simple question. Why examine cybersecurity among America's local governments? What's so special about these organizations that they deserve scrutiny? They are, after all, just organizations, and most, if not all organizations have certain similarities, especially the need to maintain effective levels of cybersecurity. The need for cybersecurity is demonstrated every day and is a common staple in the popular media. And, local governments do not differ, much if any, in the need for cybersecurity from organizations such as Microsoft, Target, Home Depot, J.P.Morgan Chase, the White House or many others. The similarity to which readers should be aware is that all of these organizations have been successfully hacked... as has a growing number of local governments"--